2021
DOI: 10.21203/rs.3.rs-601230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetrahydropalmatinee alleviates diabetic neuropathic pain by inhibiting the inflammation via p38-MAPK signaling pathway in microglia

Abstract: Object: Exploring the effect of Tetrahydropalmatine (THP) on diabetic neuropathic pain (DNP) and its possible mechanism. Methods: The type 2 diabetic (T2DM) rat models were prepared by high-fat and high-sugar feeding combined with a single small-dose intraperitoneal injection of streptozotocin (STZ). When the mechanical withdrawal threshold (MWT) and the thermal withdrawal latency (TWL) of T2DM model rats decreased to less than 85% which were judged as DNP-bearing rats. After treatment with or without THP, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…The mechanism behind this effect was the inhibition of microglia and astrocyte activation in the rats' spinal cord, subsequently reducing the expression of the toll-like receptor-4/nuclear factor kappa B (TLR4/NF-κB) signaling pathway and levels of pro-inflammatory cytokines such as tumor necrosis factor α (TNF-α), IL-1β, and IL-6 in the spinal cord. 112 Corydalis yanhusuo has anti-inflammatory and analgesic properties due to its 113 treated rats with DNP using an extract of THP and observed that it promoted a shift from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype in lipopolysaccharide-induced BV2 microglia. This extract also inhibited the activation of the p38 MAPK signaling pathway, reduced expression levels of inflammatory factors such as NO, IL-1β, IL-6, and TNF-α, increased expression level of anti-inflammatory factor IL-10, and alleviated inflammatory response around the lesions, ultimately improving pain symptoms in the rats.…”
Section: Therapeutic Mechanisms Of Analgesic Drugs (Table 1)mentioning
confidence: 99%
“…The mechanism behind this effect was the inhibition of microglia and astrocyte activation in the rats' spinal cord, subsequently reducing the expression of the toll-like receptor-4/nuclear factor kappa B (TLR4/NF-κB) signaling pathway and levels of pro-inflammatory cytokines such as tumor necrosis factor α (TNF-α), IL-1β, and IL-6 in the spinal cord. 112 Corydalis yanhusuo has anti-inflammatory and analgesic properties due to its 113 treated rats with DNP using an extract of THP and observed that it promoted a shift from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype in lipopolysaccharide-induced BV2 microglia. This extract also inhibited the activation of the p38 MAPK signaling pathway, reduced expression levels of inflammatory factors such as NO, IL-1β, IL-6, and TNF-α, increased expression level of anti-inflammatory factor IL-10, and alleviated inflammatory response around the lesions, ultimately improving pain symptoms in the rats.…”
Section: Therapeutic Mechanisms Of Analgesic Drugs (Table 1)mentioning
confidence: 99%